Respuesta :

Answer:

[tex]x=-\frac{15}{2}[/tex]

Step-by-step explanation:

Start by distributing the 6 to each of the terms in the parentheses:

6(x)+6(9)=9

6x+54=9

Subtract 54 from both sides

6x+54-54=9-54

6x=-45

Divide both sides by 6

x=-45/6

Divide the fraction by 3/3 since it is the greatest common factor of 45 and 6. Note we can only do this since 3/3 is equivalent to 1, so we are essentially dividing the fraction by 1.

x=-15/2

[tex]\huge \boxed{\tt x= - 7.5}[/tex]

Step-by-step explanation:

  • First write the equation

[tex] \to \sf6(x+9)=9[/tex]

[tex] \\ \\ [/tex]

  • Divide the 6 to 9 which is multiplying (x + 9) .

[tex] \to \sf(x+9)= \dfrac{9}{6} [/tex]

[tex] \\ \\ [/tex]

  • Divide numerator and denominator in right side by 3

[tex] \to \sf(x+9)= \dfrac{3}{2} [/tex]

[tex] \\ \\ [/tex]

  • Subtract 3/2 with 9

[tex] \to \sf x= \dfrac{3}{2} - 9[/tex]

[tex] \\ \\ [/tex]

[tex] \to \sf x= \dfrac{3 - 18}{2} [/tex]

[tex] \\ \\ [/tex]

  • After subtracting we will get our product as - 15/2

[tex] \to \sf x= \dfrac{ - 15}{2} [/tex]

[tex] \\ \\ [/tex]

Round of -15 / 2 to get product as - 7.5

[tex] \to \sf x= - 7.5[/tex]

Verification:

6(x+9)=9

6(- 7.5 +9) = 9

6 × 1.5 = 9

9 = 9

Hence verified ~☆